1997
DOI: 10.2307/30141229
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococci in Stool Specimens Submitted for Clostridium difficile Cytotoxin Assay

Abstract: The prevalence of, and clinical risk factors associated with, vancomycin-resistant enterococcal colonization were investigated in patients suspected of having Clostridium difficile infection. Stools submitted for C difficile cytotoxin testing were screened for vancomycin-resistant enterococci (VRE). Isolates were speciated and characterized further by antibiotic susceptibility testing, DNA fingerprinting, and DNA:DNA hybridization for detection of specific vancomycin resistance genes. Of the 79 evaluable patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…A notable pattern in our study is that the regions with the higher incidence of CDAD (Northeast and Midwest) also exhibited higher incidence of VRE in at least half of the study period, consistent with the observation that infection with CDAD can facilitate transmission of VRE (10,11). The South had the highest incidence of MRSA and lowest incidence of VRE.…”
Section: Discussionsupporting
confidence: 73%
“…A notable pattern in our study is that the regions with the higher incidence of CDAD (Northeast and Midwest) also exhibited higher incidence of VRE in at least half of the study period, consistent with the observation that infection with CDAD can facilitate transmission of VRE (10,11). The South had the highest incidence of MRSA and lowest incidence of VRE.…”
Section: Discussionsupporting
confidence: 73%
“…the incidence rate of cDAD during this study period was 0.2%. Univariate analysis showed that the case patients were more likely than the control patients to have chronic lung diseases (29 blocker showed a protective effect to cDAD (or, 0.30; 95% ci, 0.13-0.69; p = 0.005). Among surgeries, orthopedic surgery had the greatest risk, followed by neurosurgery and gastrointestinal surgery.…”
Section: Resultsmentioning
confidence: 97%
“…This should be another reason to relegate vancomycin to a second position as the drug of choice for the treatment of CDAD. The risk of development of colonization with VRE and VRE superinfections in patients treated with oral vancomycin is already known (39,40,42).…”
Section: Discussionmentioning
confidence: 99%